Regulation of Cryptocurrencies and Blockchain Technologies National and International Perspectives - Girasa, Rosario (Palgrave Studies in Financial Services Technology,, 2018)
The book highlights the rise of Bitcoin, which is based on blockchain technology, and some of the many types of coins and tokens that emerged thereafter. Although Bitcoin and other cryptocurrencies have made national and international news with their dramatic rise and decline in value, nevertheless the underlying technology is being adopted by both industry and governments, which have noted the benefits of speed, cost efficiency, and protection from hacking. Based on numerous downloaded articles, laws, cases, and other materials, the book discusses the digital transformation, the types of cryptocurrencies, key actors, and the benefits and risks. It also addresses legal issues of digital technology and the evolving U.S. federal regulation. The varying treatment by individual U.S. states is reviewed together with attempts by organizations to arrive at a uniform regulatory regime. Both civil and criminal prosecutions are highlighted with an examination of the major cases that have arisen. Whether and how to tax cryptocurrency transactions both in the U.S. and internationally are analyzed, and ends with a speculative narrative of future developments. .